Maritime Safety Assessment: Analysis of Safety Management System (SMS), Ship Surveillance, and Ship Technical Condition - Honny Fiva Akira Sembiring (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Maritime Safety Assessment: Analysis of Safety Management System (SMS), Ship Surveillance, and Ship Technical Condition is a scientific literature review article. The purpose of this article is to develop a hypothesis of the influence of variables that will be used in further research. The objects of this research are online libraries, Google Scholar, Mendeley, Scopus, and other academic online media. The research method uses library research sourced from e-books and open-access e-journals. The results of this article are: 1) the influence of Safety Management System (SMS) Analysis on Maritime Safety Assessment; 2) the influence of Ship Surveillance on Maritime Safety Assessment; 3) the influence of Ship Technical Condition on Maritime Safety Assessment.